CORPORATE GOVERNANCE AND PUBLIC SECTOR PERFORMANCE IN NORTH CENTRAL NIGERIA - Aminat Arike ARIYO-EDU (Malete Journal of Accounting and Finance)
The persistent inefficiency of public sector performance in Nigeria has impeded the nation's progress and the effective provision of public services. Notwithstanding several initiatives to enhance governance in public institutions, challenges such as insufficient accountability, inadequate transparency, and suboptimal service delivery remain prevalent. These difficulties require in-depth investigation to reveal the influence of corporate governance on public sector performance. This study aims to evaluate the impact of corporate governance on numerous attributes of public sector performance, including efficiency, effectiveness, service delivery quality, accountability, and transparency in Nigeria. The study employs a quantitative methodology, applying multiple regression analysis to evaluate the correlation between corporate governance and public sector performance, while ANOVA is utilized to ascertain the significance of these correlations. The results indicate a robust positive association between corporate governance and the performance of the public sector. Corporate governance accounted for 57.6% of the variance in public sector efficiency (R² = 0.576), 57.7% in effectiveness (R² = 0.577), 66.6% in quality of service delivery (R² = 0.666), 45.9% in accountability (R² = 0.459), and 47.0% in transparency (R² = 0.470). The study indicates that effective corporate governance is vital for improving the performance of public sector institutions in Nigeria. It advises public sector agencies to establish comprehensive governance frameworks, conduct frequent performance evaluations, and use worldwide best practices to improve transparency, accountability, and service delivery. These would not only enhance the efficiency of the public sector but also contribute to the broader socio-economic landscape.